The Multiple Streams Framework and the problem broker. (27th April 2015) - Knaggård, Åsa
Abstract John Kingdon's Multiple Streams Framework (MSF) constitutes a powerful tool for understanding the policy process, and more specifically, agenda‐setting, through three separate streams: problems, policies and politics. This article argues that the MSF would benefit from further development of the problem stream. It introduces a clearer conception of agency into the problem stream by suggesting the inclusion of the problem broker. The problem broker is a role in which actors frame conditions as public problems and work to make policy makers accept these frames. The problem broker makes use of knowledge, values and emotions in the framing of problems. The use of these three elements is seen as a prerequisite for successful problem brokering – that is, for establishing a frame in the policy sphere. Other important factors are: persistence, access to policy makers, credibility and willingness. Problem brokers also need to know who to talk to, how and when in order to make an impact. The context, in terms of, for example, audience and national mood, is also crucial. The inclusion of the problem broker into the MSF strengthens the analytical separation between streams. According to Kingdon, policies can be developed independently from problems. The MSF, therefore, enables a study of policy generation. The inclusion of the problem broker, in the same sense, makes it possible to investigate problem framing as a separate process and enables a study of actors that frame problems without making policy suggestions. The MSF is, in its current form, not able to capture what these actors do. The main argument of this article is that it is crucial to study these actors as problem framing affects the work of policy entrepreneurs and, thereby, agenda‐setting and decision making.